THE EFFECT OF COMPANY SIZE, AUDIT TENURE, AND AUDIT COMMITTEE ON AUDIT QUALITY - Afrianti, Nurmaretha; Hutabarat, Rusmida Jun; Rachmawati, Yuni; Tobing, Shelly Farida (Program Studi Manajemen Fakultas Ekonomi Universitas Palembang, 2024)
This study aims to determine the simultaneous and partial effects on audit quality in Food and Beverage Subsector Companies Listed on the Indonesia Stock Exchange for the 2020–2023 Period consisting of factors such as company size, audit period, and audit committee. The secondary data source for this study is the financial statements of companies in the food and beverage subsector listed on the Indonesia Stock Exchange for the 2020–2023 period. A total of 21 companies that met the sample selection requirements became the research sample. Logistic regression analysis is the method used for data analysis. Based on the results of the hypothesis test, audit quality in Food and Beverage Subsector Companies Listed on the Indonesia Stock Exchange for the 2020–2023 Period is simultaneously influenced by company size, audit tenure, and audit committee. In Food and Beverage Subsector Companies Listed on the Indonesia Stock Exchange for the 2020–2023 Period, company size has a partial effect on audit quality. Audit tenure does not have a partial effect on audit quality in Food and Beverage Subsector Companies Listed on the Indonesia Stock Exchange. For the 2020–2023 Period, companies in the Food and Beverage Subsector listed on the Indonesia Stock Exchange were partially impacted by audit quality from the audit committee.